A Capability Approach to Understanding Sport for Social Inclusion: Agency, Structure and Organisations - Suzuki, Naofumi (Social Inclusion, 2017)
Despite the global diffusion of the term social inclusion, as well as the use of sport to promote it, questions have been raised regarding the extent to which sport is able to contribute to transforming the exclusive nature of the social structure. The lack of analytical clarity of the concept has not helped to address these questions. This article proposes a conceptual framework based on Amartya Sen’s capability approach, considering social exclusion as the denial of social relations that leads to serious deprivation of important capabilities. A person’s capabilities could potentially be improved through micro-, meso-, and macro-level social processes. At the micro level, sport-based social inclusion programmes could offer such social relations to varying degrees, though sport’s values are only relative to other leisure activities. The scale of impact depends primarily on the meso-level processes, in which the size and quality of each programme can be improved through organisational learning, and secondarily on the macro-level processes whereby the organisational population is institutionalised. It is argued that more research needs to be done on the meso and macro levels, as they are concerned with the ultimate potential of sport to facilitate structural transformation towards more socially inclusive society.